Optimalisasi Potensi Produk Hasil Pengolahan Susu di Mataram Milk - Meireni Cahyowati; Ariya Dwi Nugrahanto; Indra Kurniawan; Harvey Febrianta (BADAN PENERBIT STIEPARI PRESS, 2025)
Dairy milk, whether consumed directly or as a derivative product, is very close to today's society. Of the many milk derivative products, pasteurized milk is one that is increasingly in demand by the public. In this community service activity, the author provided counseling to Mataram Milk about the potential of dairy product businesses, especially pasteurized milk. The method in this activity consists of four stages, namely initial survey, literature study, delivery of materials by resource persons, and discussion. From the results of the discussion and question and answer session, it was found that the main problems faced by Mataram Milk were competition between business actors and the selection of dairy products to increase sales. To overcome this problem, the resource person mentioned the need for product additions and diversification. The resource person also provided a more complete explanation of dairy products including pasteurized milk, yogurt, cheese, milk tofu, herbal milk, ice cream, and milk pudding.